Social valuation of regulating and cultural ecosystem services of Arroceros Forest Park: A man-made forest in the city of Manila, Philippines - Arthur J. Lagbas (Journal of Urban Management, 2019)
Investment in urban green spaces such as street trees and forest park may be viewed as both sustainable adaptation and mitigation strategies in responding to a variety of climate change issues and urban environmental problems in densely urbanized areas. Urban green landscapes can be important sources of ecosystem services (ES) having substantial contribution to the sustainability of urban areas and cities of developing countries in particular. In the highly urbanized City of Manila in the Philippines, Arroceros Forest Park (AFP) is a significant source of regulating and cultural ES. In this study the perceived level of importance of 6 urban forest ES, attitude to the forest park non-use values, and the factors influencing willingness to pay (WTP) for forest park preservation were explored through a survey conducted on January 2018 to the college students (17-28 years, n=684) from 4 universities in the City of Manila. Survey showed that air quality regulation (mean=3.73) and climate and temperature regulation (mean=3.71) were the two most important urban forest ES. Binary logistic regression showed significant relationship of WTP with natural log allowance (p=0.000), air quality regulation ES and residence (p=0.007), and option value (p=0.008). The protest response was mainly influenced by economic reason and reliance to the government. The natural log of the positive WTP was weakly but highly significantly correlated with the natural log of students' allowance (r=0.193, p=0.000). Male students had higher WTP than female despite the lower allowance of male students. This study provided evidence that pro-environment decision was significantly influenced by attitude and socio-economic factors. The high importance value of air quality regulation, climate and temperature regulation, bequest value, and ecological value may be viewed as the students' demand for these urban green ES.
Keywords: 710; College students; Ecosystem services; Forest park; Social valuation; Willingness to pay highly urbanized city